ANALISIS KAPASITAS KEBIJAKAN PENYEDERHANAAN BIROKRASI - Mahtiasari, Aldina (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2023)
The demand for bureaucratic reform is the government's main concern. Bureaucratic reform is related to reform of government institutions that are rich, overlapping and inefficient. The aim of this literature review is to describe and see the extent of the simplification policy capacity of a government agency from an individual, organizational and systemic perspective. The research results show that at the individual level, there are still concerns about the quality and competence of functional officials. Apart from that, the lack of clarity in the development of career patterns is a result of not fulfilling the principles of professionalism. At the organizational level, the government needs to adjust the budget for the impact of equalizing positions. There is a mismatch between functional job descriptions and organizational functional duties. Moreover, the culture of paternalism is still inherent in the bureaucracy. At the systemic level, the work system has not been implemented according to policy objectives. Meanwhile, regarding the use of SPBE, the government's readiness, especially regional governments, still has not met the targets of the PANRB Ministry. In general, policy capacity in the readiness of government agencies to implement bureaucratic simplification is of course very diverse, especially at the regional government level.